Precipitação de estruvita a partir de biomassa algácea hidrolisada pelas vias térmica e química alcalina - Loureiro, Míriam Patrícia (2021)
The recovery of nutrients (N and P) from effluents from sewage treatment plants and their return for application in agricultural areas is an interesting alternative for the reduction of environmental impacts in addition to a reduction in the use of fertilizers. The present study aimed to study the precipitation of struvite (or hexahydrate ammonium and magnesium phosphate) from algae biomass subjected to hydrolytic treatments by thermal and alkaline chemical pathways. Samples of algae biomass were collected from two High Rate Lagoons aiming at the recovery of nutrients (N and P) through struvite precipitation. The precipitation reaction was carried out by adding MgO. MgO dosages were calculated by the molar ratio of Mg to the concentrations of total phosphorus found in the samples after hydrolysis. The algae biomass showed an average concentration of total solids of 37.34 ± 5.30 g/L and COD of 16.98 ± 0.14 gO2/L. The thermal hydrolytic processes proved to be more efficient when promoting solubilization of most compounds. The micrograph of the crystals obtained by precipitation after hydrolytic processes showed that the precipitated crystals resemble struvite crystals, except for the sample hydrolyzed at 80 ° C with a molar ratio of 1.4: 1 from Mg to P-PO4 3- . It was also possible to observe precipitate in the samples at 80 ° C and pH 10.00 molar ratio 1: 1 Mg in relation to PPO4 3- in the Imhoff cone, although no crystals were seen in the sample under the microscope. This research proved the technical feasibility of recovering N and P nutrients from algae biomass grown with sewage in treatment plants.